Does preoperative transarterial embolization decrease blood loss during spine tumor surgery?. Issue 1 (February 2015) - Qiao, Zhihong; Jia, Ningyang; He, Qian
This paper aimed to evaluate the effect of preoperative transarterial embolization (TAE) on estimated blood loss (EBL) during surgical excision of the vertebral tumors. Three hundred and forty-eight patients with spinal tumors were retrospectively analyzed. The preoperative TAE group consisted of 190 patients and the control group consisted of 158 patients. Gelatin sponge particles mixed withy contrast agent were used in the TAE group to embolize the tumor-feeding artery. The factors evaluated included: the time interval between embolism and surgery; the number of vertebrae involved by the tumor; pathological type of tumor; surgical approach; extent of excision and instrumental fixation. The time interval (P = 0.4669)between embolism and surgery had no significant correlation with EBL during surgery. The pathological diagnosis of vertebral tumor such as plasma cell myeloma, giant cell tumor, chondrosarcoma, hemangioma and metastasis had no significant correlation with EBL between the TAE group and control group during surgery, while the EBL of chordoma in the TAE group was significantly higher than that in the control group (p = 0.0254). The number of vertebrae involved (p = 0.4669, 0.6804, 0.6677), posterior approach (p = 0.3015), anterior approach (p = 0.2446), partial excision (p = 0.1911) and instrumental fixation (p = 0.1789) had no significant correlation with EBL during surgery between the TAE group and the control group. This study showed that preoperative TAE of the spinal tumor had no significant effect on intra-operative blood loss during surgical excision of the spinal tumor. In view of the risk of embolism, this method should be carefully considered.